2015
DOI: 10.1021/acs.nanolett.5b01246
|View full text |Cite
|
Sign up to set email alerts
|

Strain Relaxation in CVD Graphene: Wrinkling with Shear Lag

Abstract: We measure uniaxial strain fields in the vicinity of edges and wrinkles in graphene prepared by chemical vapor deposition (CVD), by combining microscopy techniques and local vibrational characterization. These strain fields have magnitudes of several tenths of a percent and extend across micrometer distances. The nonlinear shear-lag model remarkably captures these strain fields in terms of the graphene-substrate interaction and provides a complete understanding of strain-relieving wrinkles in graphene for any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 59 publications
3
66
0
Order By: Relevance
“…In the position of wrinkles, the G band was a single Lorentz peak and the peak position showed a minimal (Figure b). Hence the strain was released in the vicinity of graphene wrinkles, consistent with the strain relaxation in CVD graphene grown on Co . In contrast, in the positions away from wrinkles, the G band split into G + and G − components, indicating the uniaxial (or nonequibiaxial) strain in graphene lattice (Figure b,c) .…”
supporting
confidence: 67%
“…In the position of wrinkles, the G band was a single Lorentz peak and the peak position showed a minimal (Figure b). Hence the strain was released in the vicinity of graphene wrinkles, consistent with the strain relaxation in CVD graphene grown on Co . In contrast, in the positions away from wrinkles, the G band split into G + and G − components, indicating the uniaxial (or nonequibiaxial) strain in graphene lattice (Figure b,c) .…”
supporting
confidence: 67%
“…If the reader is interested in the detection of graphene combined with the SERS effect, a further reading of the 2013 review can be found in the work of Xu et al [178]. A good way to differentiate between doping effect and subtract effect is to plot σ G versus σ 2D of the analyzed samples (this differentiation is possible because strain affects the band position by changing bond length and angles between bonds, whereas doping affects the electron-phonon coupling [179]). …”
Section: Graphenementioning
confidence: 99%
“…Actually, the amplification of the Raman signals can be ascribed to interference effects, occurring for the structure graphene/air (500 nm)/SiO 2 (300 nm)/Si (see Figure c, I); here, the 500‐nm air layer takes the place of the 500‐nm Co film removed by dewetting. The optical path of the laser beam in the air layer is similar to the common graphene/SiO 2 (~300 nm)/Si assembly (see Figure c, II), whereas no interference occurs in the graphene/Co structure (see Figure c, III).…”
Section: Resultsmentioning
confidence: 99%
“…The optical path of the laser beam in the air layer is similar to the common graphene/SiO 2 (~300 nm)/Si assembly (see Figure c, II), whereas no interference occurs in the graphene/Co structure (see Figure c, III). The last effect, together with the screening from the metallic substrate, makes the collection of the Raman modes particularly inefficient when graphene lies onto Co …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation